Who needs trust when you know everything? Dealing with information abundance on a consumer-review Web site - Duffy, Andrew (2018)
Ideas about trust have been based on information scarcity. To overcome the uncertainty associated with choice, people gather information; when that is not enough, they turn to trust in order to make a decision. Consumer-review Web sites offer information abundance, however, which demands a re-evaluation of the function of trust under such circumstances. This study uses a survey to investigate the role of trust in the traveller review site TripAdvisor. It uses five concept pairings — two measurements of experience using the site, two forms of uncertainty, two mechanisms of information-seeking, two forms of trust and two behavioural outcomes — to explore how trust operates amidst information abundance. It proposes that while consumer-review Web sites overcome primary uncertainty (risk of making a poor choice) by providing information, they produce a secondary uncertainty (inability to assess all options) based on concerns about processing the mass of information efficiently. This study finds that trust plays a role in reducing both primary and secondary uncertainty, but not in decision-making. It proposes that trust may be subsumed into information seeking on information-abundant consumer-review Web sites, and discusses implications for how trust is understood and what it means for effective reviewer sites.